2017
DOI: 10.13057/nusbiosci/n090115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of katuk (Sauropus androgynus) powder supplementation on the levels of progesterone (P4) and estradiol-17β (E2) hormones in kacang goat (Capra aegragus)

Abstract: Abstract. Putranto HD, Hasibuan GP, Yumiati Y, Ginting SM. 2017 . Effect of katuk (Sauropus androgynus) powder supplementation on the levels of progesterone (P4) and estradiol-17β (E2) hormones in kacang goat (Capra aegragus). Nusantara Bioscience 9: 86-91.Kacang goat (Capra aegragus) is one of Indonesian endemic ruminant species which commonly retained by the community in Indonesia. This species is classified as a small ruminant which has many benefits i.e easy to be domesticated and to adapt, and has an econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Improvements in pregnancy when cows were fed Ca salts of a mix of C18:2 omega-6 and transoctadecenoic fatty acids were supported by the increased fertilization and embryo quality in non-super ovulated lactating dairy cows (Cerri et al 2004). Supplementation of S. androgynus powder at a dose of about 3% can increase reproductive hormones in female kacang goat (Putranto et al 2017).…”
Section: Phytochemical Of Ethanol Extract Of Sauropus Androgynusmentioning
confidence: 97%
“…Improvements in pregnancy when cows were fed Ca salts of a mix of C18:2 omega-6 and transoctadecenoic fatty acids were supported by the increased fertilization and embryo quality in non-super ovulated lactating dairy cows (Cerri et al 2004). Supplementation of S. androgynus powder at a dose of about 3% can increase reproductive hormones in female kacang goat (Putranto et al 2017).…”
Section: Phytochemical Of Ethanol Extract Of Sauropus Androgynusmentioning
confidence: 97%
“…The methanol extract of D kutejensis leaves contains 9,12,-octadecatrienoic acid, methyl ester-a fatty acid group; these compounds are also found in the katuk (Sauropus androgynus) extract (Awaluddin et al 2020). Putranto et al (2017) reported that applying S. androgynus extract increases reproductive hormones in female goats. The ethanolic root bark extract of D. kutejensis showed cytotoxic activity (Priyadi et al 2021).…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Hal ini dapat dimaklumi mengingat pengaruh senyawa aktif dalam daun katuk yang dapat meningkatkan kadar hormonal. Putranto et al (2017) melaporkan bahwa suplementasi 3% daun katuk dalam pakan kambing kacang mampu meningkatkan kadar hormon reproduksi (progesteron dan estrogen-17β) dalam darah kambing kacang betina. Pemberian suplemen daun katuk pada kambing kacang jantan juga memerlihatkan peran hormonal, serta dapat meningkatkan produksi spermatid dan spermatosit pada testis kambing (Farasyi et al 2014).…”
Section: Pendahuluanunclassified
“…Daun katuk sudah diketahui mengandung senyawa aktif yang memiliki aksi metabolik maupun aksi hormonal, juga mengandung senyawa anabolik steroid sehingga mampu memicu sintesis protein dan pertumbuhan bobot badan ternak (Suprayogi 2016). Laporan tesebut dikuatkan oleh Putranto et al (2017) yang menguatkan bahwa suplementasi 3% daun katuk dalam pakan kambing kacang mampu meningkatkan kadar hormon reproduksi (progesteron dan estrogen-17β) dalam darah kambing kacang betina. Pemberian suplemen daun katuk pada kambing kacang jantan juga mengindikasikan peran hormonal, serta dapat meningkatkan produksi spermatid dan spermatosit pada testis kambing (Farasyi et al 2014).…”
Section: Respons Pertumbuhan Dan Karkas Pada Domba Jantanunclassified